2020
DOI: 10.1371/journal.ppat.1008843
|View full text |Cite
|
Sign up to set email alerts
|

The gammaherpesviral TATA-box-binding protein directly interacts with the CTD of host RNA Pol II to direct late gene transcription

Abstract: β-and γ-herpesviruses include the oncogenic human viruses Kaposi's sarcoma-associated virus (KSHV) and Epstein-Barr virus (EBV), and human cytomegalovirus (HCMV), which is a significant cause of congenital disease. Near the end of their replication cycle, these viruses transcribe their late genes in a manner distinct from host transcription. Late gene transcription requires six virally encoded proteins, one of which is a functional mimic of host TATA-box-binding protein (TBP) that is also involved in recruitme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…We therefore propose that while TFIIH is required for UL87 initiation, it is not a stable component of the UL87 PIC that we detect. A recent study regarding ORF24, a UL87 homolog in Kaposi’s sarcoma associated virus 20 , showed association with the Pol II CTD only in the hypophosphorylated state, which is in agreement with our data demonstrating that the Pol II in UL87 PIC is predominantly unphosphorylated 48 . Regardless of these functional differences, both PICs function on a large shared subset of HCMV promoters.…”
Section: Discussionsupporting
confidence: 93%
“…We therefore propose that while TFIIH is required for UL87 initiation, it is not a stable component of the UL87 PIC that we detect. A recent study regarding ORF24, a UL87 homolog in Kaposi’s sarcoma associated virus 20 , showed association with the Pol II CTD only in the hypophosphorylated state, which is in agreement with our data demonstrating that the Pol II in UL87 PIC is predominantly unphosphorylated 48 . Regardless of these functional differences, both PICs function on a large shared subset of HCMV promoters.…”
Section: Discussionsupporting
confidence: 93%
“…We therefore propose that while TFIIH is required for UL87 initiation, it is not a stable component of the UL87 PIC that we detect. A recent study regarding ORF24, a UL87 homolog in Kaposi's sarcoma associated virus 20 , showed association with the Pol II CTD only in the hypophosphorylated state, which is in agreement with our data demonstrating that the Pol II in UL87 PIC is predominantly unphosphorylated 45 . Regardless of these functional differences, both PICs function on a large shared subset of HCMV promoters.…”
Section: Discussionsupporting
confidence: 93%
“…Like DCP2, VACV D10 contains a Nudix hydrolase domain [ 19 ]; however, it lacks the inhibitory C-terminal domain, supporting the hypothesis that D10 may function as a constitutively active decapping enzyme. Indeed, many viruses encode proteins that functionally mimic cellular factors but have evolved to have reduced or novel regulation [ 2 4 , 20 , 21 ]. Here, we tested this hypothesis by defining the breadth of VACV D10 targets by RNA sequencing.…”
Section: Introductionmentioning
confidence: 99%